2017
DOI: 10.1111/apt.13945
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: rifaximin versus placebo for the treatment of functional dyspepsia

Abstract: Treatment with 2 weeks of rifaximin led to adequate relief of global dyspeptic symptoms, belching and post-prandial fullness/bloating in subjects with functional dyspepsia. The difference was more marked in females. (clinicaltrials.org NCT01643083).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(101 citation statements)
references
References 27 publications
2
79
0
17
Order By: Relevance
“…New treatment options are emerging based on these concepts, including anti-inflammatory drugs (at least in paediatric functional dyspepsia, montelukast (a cysteinyl leukotriene receptor 1 antagonist) has yielded promising results) 233 and non-absorbable antibiotics, such as rifaximin 234 . New data support the role of low-dose tricyclic antidepressants in functional dyspepsia, although the mechanism of action is unclear 200 .…”
Section: Discussionmentioning
confidence: 99%
“…New treatment options are emerging based on these concepts, including anti-inflammatory drugs (at least in paediatric functional dyspepsia, montelukast (a cysteinyl leukotriene receptor 1 antagonist) has yielded promising results) 233 and non-absorbable antibiotics, such as rifaximin 234 . New data support the role of low-dose tricyclic antidepressants in functional dyspepsia, although the mechanism of action is unclear 200 .…”
Section: Discussionmentioning
confidence: 99%
“…22 Other triggers have been on relapse and retreatment are not available. 30 While rifaximin's predominant effect in functional dyspepsia is believed to be antibiotic, its anti-inflammatory properties may contribute to symptom relief. 30 …”
Section: Dietmentioning
confidence: 99%
“…These findings are supported by the recent publication of a placebo-controlled trial in which treatment with the poorly absorbed antibiotic rifaximin was found to reduce symptoms in FD patients 33 .…”
Section: General Considerationsmentioning
confidence: 61%